Factors Leading to Discntinuation of Intra Uterine Contraceptive Device - Dawood, Zahida; Salam, Rohana; Dawood, Shakira; Allouddin; Malghalara; Kamal, Rabia; Bazai, Saiqa (Indus Journal of Bioscience Research, 2025)
Background: Because of their low user effort, affordability, and safety, intrauterine contraceptive devices (IUCDs) are frequently used for long-acting reversible contraception. Despite these benefits, a sizable percentage of consumers stop using IUCDs too soon. This restricts the device's ability to fully prevent unwanted pregnancies. Misconceptions, insufficient counseling, cultural attitudes, and side effects are frequently factors that contribute to discontinuation. Improving the results of reproductive health requires an understanding of these factors. Objective: The purpose of this study was to investigate the prevalence and underlying causes of IUCD discontinuation among female patients at a tertiary care facility. The goal of the study was to pinpoint prevalent patterns, user issues, and sociocultural elements that affect IUCD removal. Additionally, it sought to assess any gaps in follow-up and counseling procedures. Interventions to increase continuation rates would be supported by the findings. Promoting better informed contraceptive choices is the ultimate objective. Methodology: A tertiary care hospital in Quetta, Balochistan, served as the site of this six-month qualitative study. A semi-structured questionnaire was used for interviews with a purposive sample of 130 women who had stopped using IUCD. Descriptive statistics were used in the compilation and analysis of the data. For ease of understanding and interpretation, important discontinuation criteria were determined and displayed in frequency tables. Findings: The majority of participants were in the 26–35 age range. Myths or misconceptions concerning the device (19.2%), lower abdomen pain (23.1%), and excessive menstrual flow (29.2%) were the main causes of IUCD cessation. Significant contributions were also made by inadequate therapy (15.4%) and pressure from partners or family (7.7%). Most removals took place in the first six months following insertion. Conclusion: side effects, a lack of knowledge, and cultural misunderstandings are the main factors behind IUCD cessation. Proactive follow-up, increased counseling, and community awareness can all contribute to a decrease in premature removal and an increase in satisfaction. Improving the results of contraception requires addressing the social and psychological obstacles.